Integrating Drone Technology In Service Learning For Engineering Students - Phang, Fatin Aliah; Wong, Adam Yoon Khang; Jamil Alsayaydeh, Jamil Abedalrahim; Pusppanathan, Jaysuman; Nawi, Nina Diana; Zulkifli, Nur Amira; Che Harun, Fauzan Khairi; Tee, Kian Sek; Zulkapri, Izwyn (International Association of Online Engineering, 2021)
Future engineers shall not only good at knowledge and technology but also good at other attributes such ethical, professional as well as managing people and emotion. Service learning is an effective education model to develop more holistic engineers. However, there is a lack of service learning frame- work that integrates technology, in order to achieve the acquisition of the above attributes. This paper describes how drone technology is disseminated by engineering students to the public through a service learning programme. Document analysis of the course information, project reports, and students’ reflections were employed in this study to identify the learning process and attributes developed by the students. the students went through 6 phases of service learning implementation. Results show that the service learning has enhanced the students’ learning, sense of responsibility, accountability, and international exposure. These are essential to develop good engineers in the future.